تأثير طرق مختلفة للإنهاء والتلميع على سطح ترميمات الكمبوزيت (Latakia University Journal -Medical Sciences Series, 2017)
تهدف هذه الدراسة إلى تقييم خشونة راتنج (Tetric N Ceram "Ivoclarvivadent") بعد تطبيق تقنيات مختلفة للإنهاء و التلميع. حيث تم تصنيع 50 عينة بقياس (2×10) ملم و قسمت إلى 5 مجموعات (N=10) وذلك تبعاً للتقنية المطبقة. وقد كانت المجموعة الأولى G1: سنابل تنغستين كاربايد، و المجموعة الثانية G2: نظام Astropol ، و المجموعة الثالثة G3: أقراص Stem، و المجموعة الرابعة G4:سنابل تنغستين كاربايد يلها نظام Astropol، و أخيراً المجموعة الخامسةG5: سنابل تنغستين كاربايد يلها أقراص Stem. حيث طبقت سنبلة ماسية خشنة ، ومن ثم طبقت سنبلة ماسية فائقة النعومةعلى جميع عينات الدراسة قبل البدء بأي من اجراءات الانهاء والتلميع. و بعد اجراءات الانهاء والتلميع، تم قياس خشونة السطح (Ra µm) باستخدام جهاز Alicona-InfiniteFocus ومن ثم تم تحليل البيانات باختبار Kruskal-Wallis يليه اختبارMann-WhitneyU عند مستوى دلالة 5%.أظهرت النتائج أنه يوجد فرق معنوي بين المجموعة الثانية ( نظام Astropol) و بقية المجموعات المدروسة ، و أيضاً وجود فرق معنوي بين المجموعة الخامسة ( نظام تنغستين كاربايد يليها أقراص Steem ) وبقية المجموعات المدروسة .وفقاً للنتائج التي تم الحصول عليها نستنتج أن الراتنج المركب Tetric N Ceram حقق أقل مستوى لخشونة السطح عند استخدام أنظمة الإنهاء والتلميع المتبعة في المجموعة الثانية (Astropol)، وكذلك في المجموعة الخامسة ( سنابل تنغستين كاربايد مع أقراص Stem)، في حين حققت المجموعة الثالثة ( أقراص Stem ) أعلى مستوى لخشونة سطح الكمبوزيت. The aim of the study is to evaluate the surface roughness of the resin Tetric N Ceram (Ivoclarvivadent ) after different finishing and polishing techniques. 50 specimens of (10×2) mm were made and distributed in 5 groups (N=10), According to the technique employed: First group G1: Tengustinecarbid burs, Second group G2: Astopol system, Third group G3: Stem discs, Fourth group G4: Tengustinecarbid burs then Astropol system, Fifth group G5: Tengustinecarbid burs then Stem discs.A coarse roughness diamond bur was applied , then applied a super fine diamond bur on all specimens of the study before starting any procedure of finishing and polishing. After finishing and polishing techniques, surface roughness )Ra µm( was measured using InfiniteFocus– Alicona.Data were subjected to Kruskal-Wallis and Mann-Whitney U test at 5% significance level The results show thatthere were a significantly different between second group (astropol system ) and other groups , also a significantly different was detect between fifth group ( tengustinecarbid burs then steem discs ) and other groups .According to the obtained results, we conclude that Tetric N Ceram composite resin presented the lowest surface roughness by using finishing and polishing systems in Group2 ( Astropol system ) and Group 5 (Tengustinecarbid burs then Stem discs), while the use of Stem discs in Group 3 resulted in the highest composite surface roughness.